PELATIHAN LAPORAN KEUANGAN BERDASARKAN SAK EMKM DI UMKM NIKY COKLAT KEDIRI - Muwafida, Yumaida Tsalisa Nur; Junjunan, Mochammad Ilyas (Devote: Jurnal Pengabdian Masyarakat Global, 2024)
Micro, small, and medium enterprises have proliferated since the COVID-19 pandemic. In Indonesia, MSMEs have an important role in economic growth and contribute highly. The existence of service by providing training in opening financial reports is intended so that business actors have skills in making financial reports by SAK EMKM and are more consistent in recording transactions that occur. The findings in the implementation of this service are that business actors also do not separate personal money and business money, besides business actors are also less consistent in recording transactions that occur. The method used in this empowerment is to convey information to business actors regarding financial reports and practices. The result of this service is to provide additional knowledge about financial reports and business actors can make financial reports independently.